Морфология и коагуляция при отжиге золотых нанопленок, нанесенных на алмаз и стеклоуглерод - Найдич, Ю.В.; Габ, И.И.; Костюк, Б.Д.; Куркова, Д.И.; Стецюк, Т.В.; Дукаров, С.В.; Крышталь, А.П.; Литвин, О.С. (ИПМ НАНУ, 2008)
Исследованы изменения морфологии и коагуляционные явления, которые происходят в золотых нанопленках толщиной 200-300 нм, нанесенных на поверхности алмаза и стеклоуглерода и отожженных в вакууме при температурах до 1100 °С. Определены контактные углы смачивания в твердой фазе золотом этих материалов и показан механизм изменения морфологии пленок в зависимости от температуры отжига. . . . . . . . . . . . . Changes of morphology and coagulation phenomena which occur in gold nanofilms by thickness of 200–300 nanometers deposited onto surface of diamond and carbonglass during annealing in vacuum at temperatures up to 1100 °C are investigated. Wetting contact angles of these materials by gold in solid phase are determined and mechanism of nanofilms morphology change depending on temperature annealing is shown.
Morphology and coagulation during annealig of gold nanofilms deposited onto diamond and carbonglass
Keywords: Thin films; morphology; Wetting; Research Subject Categories::NATURAL SCIENCES::Physics::Condensed matter physics::Surfaces and interfaces